Dissection of contiguous gene effects for deletions around ERF on chromosome 19. Issue 7 (16th May 2021) - Calpena, Eduardo; McGowan, Simon J.; Blanco Kelly, Fiona; Boudry‐Labis, Elise; Dieux‐Coeslier, Anne; Harrison, Rachel; Johnson, Diana; Lachlan, Katherine; Morton, Jenny E. V.; Stewart, Helen; Vasudevan, Pradeep; et al.
Abstract: Heterozygous intragenic loss‐of‐function mutations of ERF, encoding an ETS transcription factor, were previously reported to cause a novel craniosynostosis syndrome, suggesting that ERF is haploinsufficient. We describe six families harboring heterozygous deletions including, or near to, ERF, of which four were characterized by whole‐genome sequencing and two by chromosomal microarray. Based on the severity of associated intellectual disability (ID), we identify three categories of ERF ‐associated deletions. The smallest (32 kb) and only inherited deletion included two additional centromeric genes and was not associated with ID. Three larger deletions (264–314 kb) that included at least five further centromeric genes were associated with moderate ID, suggesting that deletion of one or more of these five genes causes ID. The individual with the most severe ID had a more telomerically extending deletion, including CIC, a known ID gene. Children found to harbor ERF deletions should be referred for craniofacial assessment, to exclude occult raised intracranial pressure. Abstract : Heterozygous intragenic loss‐of‐function mutations of ERF were previously reported to cause a novel craniosynostosis syndrome. Here we describe six families harboring heterozygous deletions including, or near to, ERF . Based on the severity of associated intellectual disability (ID), we identify different categories of ERF ‐associated deletions, with the most severe when CIC, a known ID gene, is included. Children found to harbor ERF deletions should be referred for craniofacial assessment, to exclude occult raised intracranial pressure.